Impact of deceased donor multidrug‐resistant bacterial organisms on organ utilization. Issue 9 (12th March 2020) - Anesi, Judith A.; Han, Jennifer H.; Lautenbach, Ebbing; Lee, Dong H.; Clauss, Heather; Climaco, Antonette; Bilker, Warren B.; Hasz, Richard; Molnar, Esther; Alimenti, Darcy; West, Sharon; Tolomeo, Pam; et al.
Abstract : The extent to which donor multidrug‐resistant organisms (MDROs) affect organ utilization remains unclear. We performed a retrospective cohort study at 4 transplant centers between 2015 and 2016 to evaluate this question. All deceased donors who donated at least one organ were included. Exposed donors had at least one MDRO on culture. Unexposed donors had no MDRO‐positive cultures. Only cultures obtained during the donor's terminal hospitalization were evaluated. Multivariable regression was used to determine the association between donor MDRO and (1) number of organs transplanted per donor and (2) the match run at which each organ was accepted. Subsequently, we restricted the analysis to donors with MDR‐Gram‐negative (GN) organisms. Of 440 total donors, 29 (7%) donors grew MDROs and 7 (2%) grew MDR‐GNs. There was no significant association between donor MDRO and either measure of organ utilization. However, donor MDR‐GNs were associated with a significant reduction in the number of organs transplanted per donor (incidence rate ratio 0.43, 95% confidence interval [CI] 0.39‐0.48, P < .01), and organs were accepted significantly further down the match list (relative count 5.08, 95% CI 1.64‐15.68, P = .01). Though donor MDR‐GNs were infrequent in our study, their growing prevalence could meaningfully reduce the donor pool over time. Abstract : This multicenter retrospective cohort study reports that multidrug‐resistant Gram‐negative organisms specifically were associated with significantly reduced deceased donor organ utilization.